Ser Tomas Malori - enigma identiteta (Philologia, 2021)
All we know for certain about Sir Thomas Malory, the author of Le Morte Darthur, is found in his book, mostly in the closing words of the eight Tales that make up the Morte Darthur. In the explicit to the last Tale, he tells us his name, that he was a knight and a prisoner, that he wanted his readers to pray for him, and that he finished his book between 3 March 1469 and 4 March 1470. Scholars have identified five Thomas Malorys alive at about the right time, but no external evidence has been found to connect any of them with the Morte Darthur. The paper discusses five candidates for the authorship of this largest, all-inclusive version of Arthurian legend in English Medieval literature.